Rivers as Plastic Reservoirs - van Emmerik, Tim; Mellink, Yvette; Hauk, Rahel; Waldschläger, Kryss; Schreyers, Louise (Frontiers in Water, 2022)
Land-based plastic waste, carried to the sea through rivers, is considered a main source of marine plastic pollution. However, most plastics that leak into the environment never make it into the ocean. Only a small fraction of plastics that are found in the terrestrial and aquatic compartments of river systems are emitted, and the vast majority can be retained for years, decades, and potentially centuries. In this perspective paper we introduce the concept of river systems as plastic reservoirs. Under normal conditions, hydrometeorological variables (such as wind, runoff and river discharge) mobilize, transport and deposit plastics within different river compartments (e.g. riverbanks, floodplains, lakes, estuaries). The emptying of these plastic reservoirs primarily occurs under extreme hydrological conditions (e.g. storms, floods). In this paper we specifically focus on the retention mechanisms within different river compartments, and their effect on the fate of the plastics that are accumulated on various timescales. We aim to introduce the concept of rivers as (long-term) sinks for plastic pollution, and provide suggestions for future research directions.